Human chromosome 16 encodes a factor involved in induction of class II major histocompatibility antigens by interferon gamma. - Bono, M R (1991)
Interferon gamma (IFN-gamma) induces expression of class II major histocompatibility complex (MHC)-encoded antigens in immunocompetent cells. To gain further insight into the mechanism of this induction, we prepared somatic cell hybrids between different human cell lines and a murine cell line, RAG, that does not express murine class II MHC antigens before or after treatment with murine IFN-gamma. Some of the resulting cell hybrids express murine class II MHC antigens when treated with murine IFN-gamma. This inducible phenotype is correlated with the presence of human chromosome 16. It has been shown previously that the induction of class I MHC antigens by human IFN-gamma in human-rodent hybrids requires the presence of species-specific factors encoded by chromosome 6, which bears the gene for the human IFN-gamma receptor, and chromosome 21, whose product(s) is necessary for the transduction of human IFN-gamma signals. In this report, we show that the induction of murine class II MHC antigens by human IFN-gamma in the human-RAG cell hybrids requires, likewise, the presence of human chromosomes 6 and 21, in addition to chromosome 16. In some of these hybrids, when all three of these human chromosomes were present, induction of cell-surface HLA-DR antigens was also observed. Our results demonstrate that human chromosome 16 encodes a non-species-specific factor involved in the induction of class II MHC antigens by IFN-gamma.